Investigation on Viability of Solar Panel Covered Carpark Project for Inti International University - Tan, Chih Yong; Seyed, Amirmostafa Jourabchi; Ng, Hoon Kiat; Gan, Suyin (INTI International University, 2019)
This project aimed to study feasibility of implementing solar panels into Inti International University, Nilai academic block carpark area, forming solar carports. Capital calculation as well as breakeven calculation for the whole project are predicted in order to examine viability of project in long run. First of all, measurement of planned covered parking area was carried out and estimated total covered area is about 8520m^2 to cover 822 parking slots. A shading analysis has been carried out on planned covered area as shading impact may affect performance of panels and creating hotspot on shaded cells and eventually damage solar cells. Based on above, parking area located near sport facilities of Inti Academic Block were considered. Carports structure to cover such area has been designed and cost of carports structure is about RM190k. For solar system, a real quotation has been requested from Solar Company named Plus Solar in order to obtain an accurate calculation of capital where solar system consists of 72 pieces of JA Solar 375Wp Monocrystalline panels, forming a 27kwp (kilowatt-peak) solar system that potentially saves an average of RM 15k per year. As cost for solar system is RM 194,400, the total capital of this solar carport project is approximately RM 465k. By considering tax incentives provided by government including GITA & CA tax incentives, and in addition consideration of 0.65% for annual derating of solar system and 3% of increment for OPEX annually, as well as RM 14,924.29 of average annual electricity bills saving (for 30year), and this solar carport project requires 25 years and 2 months (25.17years) to reach its breakeven point.